Perancangan Prototype Sistem Manajemen Quiz Berbasis Web Untuk Mendukung Evaluasi Pelatihan Menggunakan Figma - M.Robi Maulana; Usman Ependi (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
The development of information technology has provided convenience in supporting training activities and competency evaluation within companies. Training is one of the important activities carried out to improve participants’ knowledge, skills, and abilities in accordance with organizational needs. To determine the success of training, an evaluation process is required to measure participants’ level of understanding of the material that has been delivered. Based on observations conducted at a company, the training evaluation process still requires a more structured, interactive, and user-friendly medium. The company’s identity is not directly disclosed due to its confidentiality policy; therefore, the research object in this article is referred to as Company X. This study focuses on designing a prototype of a dashboard Quiz Management System using Figma. The system is designed to support question management, quiz library, quiz implementation through QR Code, quiz result presentation, question discussion, and leaderboard features. The purpose of this study is to produce a prototype design that can serve as an initial reference for developing a web-based training evaluation system that is more modern, structured, interactive, and suitable for user needs.